PERHITUNGAN BEBAN DEPRESIASI AKTIVA TETAP MENGGUNAKAN METODE SALDO MENURUN GANDA PADA CV. SUMBER AGUNG - Tedi Rochendi; Sugiyono Sugiyono (Institut Teknologi dan Bisnis Swadharma, 2020)
Depreciation or depreciation is a process in which the cost of fixed assets becomes a cost over their useful life. Fixed assets will continue to be depreciated each period until their useful life ends. An estimate of the life of the asset is required to assess the useful life of the asset. The estimation of the life of the fixed assets is very important because it relates to the depreciation expense of the fixed assets which will be followed up when the useful life of the assets ends, whether to be sold back or written off and other actions. In the company's operational activities, the process of acquiring fixed assets certainly requires certain considerations because errors in choosing how to acquire fixed assets will affect the company's operational activities, especially in terms of funds. For that we need a proper planning, regarding what policies need to be taken to acquire fixed assets. CV. Sumber Agung is an outsourcing company that provides workers who are knowledgeable and experienced in the construction aspect and others who are supported by professional staff. In the classification of assets in accordance with proper theory and function, CV. Sumber Agung uses the depreciation method or multiple declining balance depreciation to calculate the depreciation of its fixed assets. The choice of the method of depreciation or depreciation is because the goods they have are varied